Hubungan Mutu Pelayanan dengan Kepuasan Pasien di Instalasi Rawat Inap Rumah Sakit Ibnu Sina YW-UMI - Fridawaty Rivai; Syalwinda Lestari; Khalid Shaleh (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Making patients satisfaction as the main orientation is one of the characteristics of quality health service. This study aims to analyze patient satisfaction in relation with respondent characteristics and dimensions of service quality. This research was quantitative study with cross sectional approach on Ibnu Sina Hospital. Sample obtained were 242 people selected by consecutive sampling. Data obtained through the results of the distribution of questionnaires which were then analyzed using the Spearman correlation test. The dimensions of technical competence (p = 0.026), effectiveness, efficiency, service continuity, safety, and interpersonal relations with (p = 0.000) were dimensions that have significant relation. The dimensions of access to services (p = 0.177) and amenities (p = 0.516) were dimensions that have not a significant relation with patient satisfaction. There is a significant relationship in six of the eight dimensions of service quality. Suggestions for this study to improve the aspects of nurses' attitudes and skills, nurse awareness to identify patients, alacrity to patients, communication skills, especially nurses in conveying patient's condition to the doctor, and educate patient about risk accident at the hospital.